Clinical profile of patients with infantile tremor syndrome in a tertiary care center - Pathak, Gargi H.; Chauhan, Anuya V.; Pandya, Dhruti (International Journal of Contemporary Pediatrics, 2020)
Background: Infantile tremor syndrome (ITS) is a condition reported from many areas of Indian subcontinent due to lack of proper nutrition, improper weaning or delayed introduction of complementary feeding. There is no proven macro or micro nutrient deficiency responsible for it but relation with vitamin B12 deficiency has been identified in some studies. The aim of this study was to study the clinical profile of patients with ITS. Methods: It is a prospective observational study including total 30 patients, from 6 months to 3-year age group, admitted to pediatric wards and nutritional rehabilitation centre, civil hospital, Ahmedabad, from June 2018 to December 2019. Results: Out of 30 patients studied, 69% had pre-ITS and rest had ITS, 61.5% were males and 38.4% were females, 69.2% had severe acute malnutrition, 84.6% had severe anemia and 23% of them presented with CCF, 15.4% patients had microcephaly and 23% had hypotonia. 23% had motor and speech delay. 61.5% belonged to lower socio-economic group. There was delayed introduction of complementary feeding in 63% of patients. 69% patients had severe vitamin B12 deficiency and 21% had moderate vitamin B12 deficiency. Conclusion: ITS, is commonly seen among male children belonging to lower socio-economic group among age group of 6 months to 24 months, presents with coarse tremors with moderate to severe anemia with moderate to severe acute malnutrition and is associated with deficiency of vitamin B12. Early diagnosis and treatment including nutritional rehabilitation grossly improved the outcome.